2023
DOI: 10.1088/1402-4896/ace564
|View full text |Cite
|
Sign up to set email alerts
|

Pristine and modified silicene based volatile organic compound toxic gas sensor: a first principles study

Shazia Showket,
Khurshed A Shah,
G N Dar

Abstract: In this work, we have investigated the sensitivity of two Volatile Organic Compounds (VOCs), formaldehyde (FD) and acetaldehyde (AD) on the surface of two-dimensional (2D) Armchair Silicene Nanoribbon (ASiNR) by analysing the structural, electronic and transport properties using density functional theory (DFT) and non-equilibrium Green's function (NEGF) formalism. Different models of ASiNR have been considered viz; pristine, Al-doped, P-doped, Al/P co-doped and vacancy-defected ASiNR. The findings revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In theoretical research, silicene and other nanostructures can be studied by employing the popular classical molecular dynamics simulation [16]. Unfortunately, we did not find interatomic potential to accurately characterize the unique properties of silicene, for example, the low-bending structure and corresponding torsional distance that emerge through reproducing experiments [17] and preliminary calculations [18]. From early studies, Ge was thought to form a single-layer hexagonal lattice called germanene [19].…”
Section: ‫للغاية‬ ‫الرقيق‬ ‫الجرمانيين‬ ‫و‬ ‫للسيليسين‬ ‫ارية‬ ‫الكهر...mentioning
confidence: 96%
“…In theoretical research, silicene and other nanostructures can be studied by employing the popular classical molecular dynamics simulation [16]. Unfortunately, we did not find interatomic potential to accurately characterize the unique properties of silicene, for example, the low-bending structure and corresponding torsional distance that emerge through reproducing experiments [17] and preliminary calculations [18]. From early studies, Ge was thought to form a single-layer hexagonal lattice called germanene [19].…”
Section: ‫للغاية‬ ‫الرقيق‬ ‫الجرمانيين‬ ‫و‬ ‫للسيليسين‬ ‫ارية‬ ‫الكهر...mentioning
confidence: 96%
“…Qin et al have evaluated the effect of the number of layers on the recovery rate of the WS 2 for ammonia detection and found that the recovery time linearly decreased with the decrease of the number of layers with the fast recoverable time for the WS 2 monolayer at room temperature [18]. On the other hand, several theoretical studies demonstrated that surface modification can significantly amplify the mutual interaction between the monolayer and gas molecules, thereby elevating the chemical interactions between the host layer and target molecules leading to a heightened sensitivity of the monolayer [19][20][21][22]. In recent research, it has been found that the introduction of Ni into WS 2 can significantly enhance the adsorption energy of H 2 , CO, and C 2 H 2 , leading to significant chemical reactions accompanied by a decrease in the band gap, specifically associated with the adsorption of C 2 H 2 .…”
Section: Introductionmentioning
confidence: 99%